ISLAMIC STUDIES TEACHERS’ ACCEPTANCE OF MOBILE LEARNING IN ILORIN SOUTH LOCAL GOVERNMENT AREA OF KWARA STATE, NIGERIA - Kamilu Olanrewaju, Muraina; Muhammad Jamiu, Issa (Al-Mudarris: Journal Of Education, 2023)
The increased accessibility to mobile networks coupled with a decrease in the cost of mobile devices has significant implications for transforming the educational instructional environment, particularly in the area of m-learning. Against this background, the study examined Islamic Studies teachers’ acceptance of mobile learning in Ilorin South Local Government Area of Kwara State, Nigeria. Descriptive research method was adopted for this study. The population for this study was all Islamic studies teachers in Ilorin South Local Government Area of Kwara State Nigeria. One hundred and twenty teachers of Islamic Studies were selected as respondents for this study using purposive sampling technique. A researcher- designed questionnaire was used. Research questions were answered using mean and percentage at an alpha level of 0.05. Finding of this study revealed that the level of acceptance of mobile phones in teaching of Islamic studies in Ilorin South Local Government Area of Kwara State, Nigeria was high 115 (95.8%). Teachers of Islamic studies used mostly Internet, Video Camera, Taking Note and others respectively. Teachers of Islamic studies also used of mobile phones application very frequently, frequently, sometimes, and not at all teaching and learning of Islamic studies. Based on these findings, the study concluded that the level of acceptance of mobile phones in teaching of Islamic studies in Ilorin South Local Government Area of Kwara State, Nigeria was high. The study recommended based on the findings that government at all levels should assist in the provision of more modern mobile phones in secondary schools for teaching of Islamic Studies.